2016
DOI: 10.1177/1059840516654743
|View full text |Cite
|
Sign up to set email alerts
|

Handling Demands of Success Among Girls and Boys in Primary School: A Conceptual Model

Abstract: Stress among adolescents in Western societies is becoming an issue of increasing concern, and the global trend of adolescents' health shows a gradual deterioration that is independent of national differences and increases with age. The aim of this study was to explore the main concern of adolescents and about how they cope with demands in everyday life. Participants were 14-16 years old, and data were collected from three sources. A constructivist grounded theory was used as a method for generating a model of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…The girls in our study generally perceived greater demands from school, and such demands have been found to have a negative impact on their health (Inchley & Currie, 2016; Låftman & Modin, 2012; Plenty et al, 2014; Wiklund et al, 2012). The boys expressed a more relaxed attitude toward demands and the future, which concurs with findings in earlier studies (Banks & Smyth, 2015; Wilhsson et al, 2016). This may be one of the several explanations for the differences between the attitudes of girls and boys toward demands and the future in our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The girls in our study generally perceived greater demands from school, and such demands have been found to have a negative impact on their health (Inchley & Currie, 2016; Låftman & Modin, 2012; Plenty et al, 2014; Wiklund et al, 2012). The boys expressed a more relaxed attitude toward demands and the future, which concurs with findings in earlier studies (Banks & Smyth, 2015; Wilhsson et al, 2016). This may be one of the several explanations for the differences between the attitudes of girls and boys toward demands and the future in our study.…”
Section: Discussionsupporting
confidence: 91%
“…A new research question was formulated from data previously collected by the first author (M.W.) in 2013-2014 and studied on the subject, how adolescent handle their everyday life (Wilhsson, Svedberg, Högdin, Carlsson, & Nygren, 2016). This research is a secondary analysis and is a way of using preexisting research data for investigating new questions that were not the aim of the original data collection (Å kerström, Jacobsson, & Wästerfors, 2004).…”
Section: Design and Settingsmentioning
confidence: 99%
“…Previous research has shown that social norms can contribute to health behaviours among adolescents. Incentives such as appearance and social popularity in specific social groups can motivate physical activity and dietary habits, resulting in perceptions of success (Wilhsson et al, 2017). In addition, engagement in health risk behaviours can be based on avoidance of social vulnerability rather than health risks (Randell et al, 2016;Van Amsterdam & Knoppers, 2018) as smoking and drinking alcohol has shown to strengthen the sense of belonging with friends (Randell et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Money was also viewed as important to success. In some instances this was related to achieving wealth and the status associated with being rich (Hershberg et al, 2014;Trask-Kerr et al, 2019;Wilhsson, Svedberg, Carlsson, Hogdin, & Nygren, 2017). For many, however, it seemed to be more connected to earning enough to be financially secure or living comfortably (Hoskins & Barker, 2017;Joos, 2003;Trask-Kerr et al, 2019).…”
Section: Success Perceptions: Qualitative Studiesmentioning
confidence: 99%
“…Status was also important to a small number of participants in two of the studies reviewed (Hoskins & Barker, 2017;Wilhsson et al, 2017). This was envisaged as being popular, projecting the right image (fashion or physical appearance), accumulating wealth, or succeeding in sport or business.…”
Section: Success Perceptions: Qualitative Studiesmentioning
confidence: 99%